Activity levels after reverse shoulder arthroplasty - Bülhoff, Matthias; Sowa, Boris; Bruckner, Thomas; Zeifang, Felix; Raiss, Patric (Archives of orthopaedic and trauma surgery, 2016)
Aim of this study was to analyze whether patients undergoing reverse shoulder arthroplasty (RSA) surgery are able to successfully return to sports and afterwards.
Gesehen am 20.05.2020